Implementasi Pembelajaran Berdiferensiasi Pendidikan IPS di SMA Muhammadiyah 1 Purbalingga Sebagai Upaya Meningkatkan Critikal Thinking Skill - Fauzi Nur Akhadi; Sriyanto Sriyanto (UM Purwokerto Press, 2023)
The background of this research is that there are still many social studies teachers who convey learning conceptually and are dominated by the lecture method. This condition causes a lack of students' ability to solve existing problems and students will be ignorant of existing learning materials. The differentiated learning model is an alternative learning model that can be used to convey material in an interesting way and has continuity with the independent learning curriculum which has an impact on increasing critical thinking skills. In the learning process it has been able to improve Critical Thinking Skills in students. This can be seen in a conducive and interactive classroom atmosphere. Students' curiosity increases in the number of student questions asked to the teacher during presentations. learning strategies implemented based on content, process and product differentiation. This content differentiation students can use various methods according to their learning style. Process differentiation arises during group learning activities. Students are given assistance according to their needs in completing worksheets prepared by the teacher. Product differentiation is carried out by giving assignments to students to choose works that will be given to teachers according to student interests. However, there are still obstacles in its application because some teachers feel they are not ready to apply this learning method besides the low interest in student learning.